The degree of possession of basic education teachers’ knowledge of interactive digital education skills and it's applications (Journal of Hama University, 2026)
The research aimed to identify " The level of basic education teachers’ knowledge of interactive digital education skills and its applications." The differences between the teachers' answers are defined according to the research variables: (gender, years of experience, training courses). The research relied on the analytical descriptive approach, and the researcher used the questionnaire tool to collect data. The research sample included (85) A male and female basic education teacher in the schools of the city of Damascus. The research reached the following results:The level of knowledge of basic education teachers about interactive digital education skills and its applications is average. The average of teachers’ answers to the questionnaire as a whole was (2.14) and a percentage of (71%).- There are no statistically significant differences between the average scores of teachers on the research questionnaire due to the variables of gender.- There are no statistically significant differences between the average scores of teachers on the research questionnaire due to the years of experience variable. Except for the axis (knowledge of interactive digital education applications), there were statistically significant differences in favor of teachers with years of experience (more than 10 years).- There are no statistically significant differences between the average scores of teachers on the research questionnaire due to the training courses variable. Except for the variables of knowledge of interactive digital education applications and knowledge of interactive digital education concepts, there are differences in favor of teachers who followed two or more courses.- The most widely used electronic applications in education: PowerPoint, electronic tests, virtual meetings, and montage and video editing programs.The research reached a number of recommendations and proposals.